Empowering the 'shamed' self: Recognition and critical social work. (January 2016) - Houston, Stan
Summary: This article provides a review of the contribution of Axel Honneth's model of recognition for critical social work. While Honneth's tripartite conceptualisation of optimal identity-formation is positively appraised, his analysis of the link between misrecognition, the experience of shame and eventual sense of moral outrage, is contested. Drawing on a range of sources, including the sociology of shame, Honneth's ideas about the emotional antecedents of emancipatory action are revised to guide critical social work with misrecognised service users. Findings: The intellectual background to Honneth's recognition model, emanating from leading German philosophers, is described and its application to social work set out. Even so, Honneth's model is found to be deficient in one primary regard: its assumption about the emotional antecedents to quests for withheld recognition is misapprehended. In particular, the argument in this article is that the ubiquitous emotion of shame, which Honneth argues flows from misrecognition, must be carefully addressed through the medium of relationship, otherwise it might lead to repressed shame and frustrated attempts at social struggle. To this end, a social work process is delineated for dealing with shame, following episodes of misrecognition. Applications: Honneth's model of recognition, along with revised ideas about how to recognise and manage shame, is incorporated into a conceptual framework for critical social work practice. With this renewed understanding of the impact of shame, following misrecognition, social workers should be better equipped conceptually to enable service users to take action for empowerment.